(untitled) (Revista de Ciências Agroveterinárias, 2022)
Azadirachta indica is a tree that has several socioeconomic and environmental benefits. However, studies on the production of seedlings of this forest essence are scarce. The present work aimed to evaluate the influence of seven substrates on the growth of A. indica seedlings, produced in polyethylene plastic pots. The substrates were combinations of coarse sand, clay, poultry bed, bovine manure, organic matter from vegetables and wood sawdust. According to randomized block design, the experiment was set up at the Mozambique Agricultural Research Institute (IIAM), Lichinga Agricultural Station, with five repetitions. Starting 30 days after sowing, height and collar diameter were measured fortnightly. At 120 days, the variables aerial, root and total dry mass and seedling quality indices were quantified. For the variables analysed, the best results were obtained using the substrate 25% coarse sand + 50% organic matter from vegetables + 25% poultry bed, being this substrate strongly recommended to produce A. indica seedlings.